Successful Use of Tissue Plasminogen Activator in an Adolescent Male with Pyogenic Liver Abscess - Janine Zee-Cheng; Thomas Fox; Sonal Patel; Samer Abu-Sultaneh (Case Reports in Critical Care)
Large pyogenic liver abscess is a rare and difficult to treat entity in pediatric patients. Percutaneous drainage rather than open surgical drainage has become more common in recent years, even for large abscesses. Percutaneous drainage can be complicated by catheter obstruction. We present the case of a 16-year-old male presenting with abdominal pain, fever, and chills. He was diagnosed with a 9-centimeter liver abscess. A CT-guided percutaneous drainage was placed. The catheter initially drained well, but then became occluded. Tissue plasminogen activator was instilled into the catheter every 6 hours for a total of five doses, resulting in increased drainage and improved clinical state of the patient. To our knowledge, this is the first reported use of tissue plasminogen activator in pyogenic liver abscess in the pediatric population.